IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATERI IMAN KEPADA RASUL KELAS XI DI SMKM 7 GONDANGLEGI - Ansori, Isa; Muslimin, Imam; Amrullah, Abdul Malik Karim (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This classroom action research aims to improve student learning outcomes by improving the learning process in Islamic Religious Education subjects, through the Discovery Learning model and finding out how much interest they have. This classroom action research was conducted at SMKM 7 Gondanglegi with the research subjects being class XI students with a total of 29 students. This research is a type of classroom action research. The research was carried out in 3 cycles. The steps of this research begin with a pretest with the next stage being a posttest, to determine the understanding and learning success that students have achieved. From the research results it can be concluded that the application of Discovery Learning in PAI subjects can improve the learning outcomes of class XI students at SMKM 7 Gondanglegi. This increase can be seen from the average post test score for cycle I, namely 75.3 with a completion score reaching 65.5%. In cycle II there was an increase with the average post test score being 78.04 with a completeness score reaching 79.3%. Meanwhile, in cycle III, the change in scores was very significant, the average post test score was 83.8 with a completeness score reaching 93.1%. Thus, the application of the Discovery Learning model is considered successful in improving student learning outcomes in PAI material because it has achieved the predetermined success indicator, namely 75%.